The Feasibility of Less-Invasive Bentall Surgery: A Real-World Analysis - Antonia van Kampen; Christian D. Etz; Josephina Haunschild; Martin Misfeld; Piroze Davierwala; Sergey Leontyev; Michael A. Borger (Life, 2023)
Objective: Minimally invasive approaches are being used increasingly in cardiac surgery and applied in a wider range of operations, including complex aortic procedures. The aim of this study was to examine the safety and feasibility of a partial upper sternotomy approach for isolated elective aortic root replacement (a modified Bentall procedure). Methods: We performed a retrospective analysis of 768 consecutive patients who had undergone isolated Bentall surgery between January 2000 and January 2021 at our institution, with the exclusion of re-operations, endocarditis, acute aortic dissections, and root replacement with major concomitant procedures such as multi-valve or coronary bypass surgery. A total of 98 patients were operated on via partial sternotomy (PS) and were matched 2:1 to 196 patients operated on via full sternotomy (FS). Results: The procedure time was 12 min longer in the PS group (205 min vs. 192.5 min in the FS group, p = 0.002), however, cardiopulmonary bypass and aortic cross-clamp times were comparable between groups. Eight PS-procedures were converted to full sternotomy, predominantly for bleeding complications (n = 6). Re-exploration for acute bleeding was necessary in 11% of the PS group and 4.1% of the FS group (p = 0.02). Five FS patients and none in the PS group required emergency coronary bypass grafting for postoperative coronary obstruction (p = 0.2). PS patients were hospitalized for a significantly shorter period (9.5 days vs. 10.5 days in the FS group, respectively). There were no significant differences regarding in-hospital (p = 0.4) and mid-term mortality (p = 0.73), as well as for other perioperative complications. Conclusions: Performing Bentall operations via partial upper sternotomy is associated with similar perfusion and cross-clamp times, as well as overall mortality, when compared to a full sternotomy approach. A low threshold for conversion to full sternotomy should be accepted if limited access proves insufficient for the handling of intraoperative complications, particularly bleeding.